An Alternative Framework for Foreign Exchange Risk Management of Sovereign Debt - Melecky, Martin (World Bank, Washington, DC, 2012)
This paper proposes a measure of synchronization in the movements of relevant domestic and foreign fundamentals for choosing suitable currency for denomination of foreign debt. The selection of explanatory variables for exchange rate volatility is motivated using a New Keynesian Policy model. The model predicts that not only traditional optimal currency area variables, but also variables considered by the literature on currency preferences, such as money velocity, should be relevant for explaining exchange rate volatility. The findings show that measures of inflation synchronization, money velocity synchronization, and interest rate synchronization can be useful indicators for decisions on the currency denomination of foreign debt.